2010
DOI: 10.1016/j.tube.2010.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Individual Mycobacterium tuberculosis universal stress protein homologues are dispensable in vitro

Abstract: SummaryMycobacterium tuberculosis has 10 universal stress proteins, whose function is unknown. However, proteomic and transcriptomic analyses have shown that a number of usp genes are significantly upregulated under hypoxic conditions and in response to nitric oxide and carbon monoxide, as well as during M. tuberculosis infection of macrophage cell lines. Six of these USPs are part of the DosR regulon and this, along with their expression pattern and the phenotypes of usp mutants in other bacterial species, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 73 publications
(81 reference statements)
1
60
1
Order By: Relevance
“…All other USPs have either two tandem USP domains or are associated with other domains of unknown function. The single USP present in Mycobacterium leprae, ML1390, is the ortholog of Rv1636 sharing 89% identity (55). Shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All other USPs have either two tandem USP domains or are associated with other domains of unknown function. The single USP present in Mycobacterium leprae, ML1390, is the ortholog of Rv1636 sharing 89% identity (55). Shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The role of USPs in response to several stress conditions was better elucidated in other bacteria, including Escherichia coli (Gustavsson et al, 2002; Nachin et al, 2005) and Salmonella typhimurium (Liu et al, 2007; Bangera et al, 2015), Haemophilus influenzae (Fleischmann et al, 1995; Sousa and McKay, 2001), Mycobacterium tuberculosis (O'Toole and Williams, 2003; Drumm et al, 2009), Pseudomonas aeruginosa (Boes et al, 2008), and Lactobacillus plantarum (Licandro-Seraut et al, 2008; Gury et al, 2009). In all cases, the expression of USP has been associated to the arrest of cellular growth in response to prolonged stress (Hingley-Wilson et al, 2010). Nyström and Neidhardt (1992, 1994) showed that the survival of E. coli was reduced in the uspA -mutated strains.…”
Section: Discussionmentioning
confidence: 99%
“…These reports provide further evidence that UspA may be an important component of and even mechanistically linked to many different stress responses. The tuberculosis genome contains 10 different Usp-type proteins with apparent functional redundancy, but data suggest that there may be incomplete redundancy of particular Usp proteins for different stresses (65,66). The data linking Rv2623 to chronic infection indicate this protein may have a specific importance in the infection process that cannot be replicated by other Usp proteins.…”
Section: Resultsmentioning
confidence: 99%